Supernumerary teeth: A pictorial review and revised classification - Christy Lana Davidson; Chané Smit; Sulette Nel (Journal of Oral Biology and Craniofacial Research)
Current literature regarding supernumerary teeth poses the risk of confusion as ambiguity in the terminology and classification of supernumerary teeth permits differing interpretations.Uncertainty in this regard distorts data on the true incidence and prevalence of supernumerary teeth. This pictorial review provides an overview of the current understanding regarding the development of supernumerary teeth, their positional and morphological classification, and eruptive alterations. We highlight the ambiguity in defining supernumerary teeth and propose an updated classification for the description of these teeth.